The debate on the legal character of the law of nations in Spanish America during the 19th Century: The contrast between José Silva Santisteban and Andres Bello - Rosales Zamora, Pablo (2020)
The evolution of law of nations in Spanish America during the 19th century has been few studied. The present work has as aim covering that gap with the analysis on the José Silva Santisteban and Andres Bello´s approaches on the legality of international law. This article Will hold that the first author conceives properly international law as law, in contrast to the second one, who considers it only as a “collection of laws”. For understanding this debate, the article will resort to the works of Becker Lorca and Richard Morse, holding Silva Santisteban represented a neo-thomist perspective and, by the contrary, Bello sustained a utilitarian and empiricist approach of international law.